2023
DOI: 10.7759/cureus.35652
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Preoperative Ultrasonographic Airway Assessment in Predicting Difficult Laryngoscopies in Adult Patients

Abstract: Background and objectivesPresently, neck ultrasonography is used as a tool to predict a difficult airway. There are no standardized ultrasonographic criteria that help to predict a difficult airway. This study aims to ultrasonographically assess the anterior neck soft tissue thickness preoperatively based on two parameters-the minimal distance from the hyoid bone to skin (DSHB) and the distance from the skin to the epiglottis midway between the hyoid bone and thyroid cartilage (DSEM)-and find out whether these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…They concluded that both have very strong statistical significance, and DSHB seemed to have a better diagnostic value for predicting a difficult airway in their study. [ 7 ] We found similar results; however, we measured distances at the hyoid bone and thyroid isthmus levels. Both were more in the difficult laryngoscopy group, with DSTI being a better predictor of a difficult airway.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…They concluded that both have very strong statistical significance, and DSHB seemed to have a better diagnostic value for predicting a difficult airway in their study. [ 7 ] We found similar results; however, we measured distances at the hyoid bone and thyroid isthmus levels. Both were more in the difficult laryngoscopy group, with DSTI being a better predictor of a difficult airway.…”
Section: Discussionsupporting
confidence: 69%
“…[ 4 5 6 ] Pre-operative ultrasound measurement of the anterior neck soft-tissue thickness at various levels, in combination with the standard screening tests and assessment tools for difficult laryngoscopy, may enhance the prediction of difficult laryngoscopy. [ 7 8 ]…”
Section: Introductionmentioning
confidence: 99%
“…Bhagavan et al [9] performed a pre-anesthetic ultrasound airway assessment. They concluded that distance from skin to epiglottis midway (DSEM)-thickness of anterior neck soft tissue in the transverse view at the level of the thyrohyoid membrane with a cut-off at 2.03 cm correlated positively with difficult laryngoscopy.…”
Section: Discussionmentioning
confidence: 99%